Stack sizing for optimal current drivability in subthreshold circuits - Kim, Tony Tae-Hyoung (2010)
Subthreshold circuit designs have been demonstrated to be a successful alternative when ultra-low power consumption is paramount. However, the characteristics of MOS transistors in the subthreshold region are significantly different from those in strong inversion. This presents new challenges in design optimization, particularly in complex gates with stacks of transistors. In this paper, we present a framework for choosing the optimal transistor stack sizing factors in terms of current drivability for subthreshold designs. We derive a closed-form solution for the correct sizing of transistors in a stack, both in relation to other transistors in the stack, and to a single device with equivalent current derivability. Simulation results